Prospecting and Characterizing Efficient Phthalate Esters (PAEs) Utilizing Fungi from Contaminated Soil - Puranik, Shriniketan; Shukla, Livleen (International Journal of Bio-resource and Stress Management, 2022)
The present study was conducted during August 2020 involving twenty-nine fungi isolated from PAE-contaminated soils [viz. sanitary landfill, Bhalswa (SLF) and Centre for Protected Cultivation (CPCT), ICAR-IARI, New Delhi. The objective of the study was to qualitatively screen the isolates for enzyme production (laccase and esterase) and phthalate ester (PAE) tolerance limits. For laccase production, the isolates were inoculated on malt extract, while esterase production was determined using tributyrin agar. Furthermore, radial growth of isolates on plates supplemented with different concentrations (100, 500 and 1000 mg l-1) of di-n-butyl phthalate (DBP) and di (2-ethylhexyl) phthalate (DEHP) was done to assess tolerance limits. Results revealed that, out of twenty-nine fungi, except for two which produced laccase (CDEHP1 and SDBP2), all the other isolates were able to produce esterase. Six isolates each for DBP and DEHP, were able to tolerate high concentration of PAEs (up to 1000 mg l-1), and selected for further work. The results indicated that, at 14 days of inoculation, isolate SDBP4 showed highest radial growth at all concentrations of DBP. In case of isolates grown on plates supplemented with DEHP, radial growth was observed to be in the order SDEHP2>SDEHP1>SDEHP4>SDEHP5>SDEHP3>CDEHP6. Also, physicochemical properties of the contaminated soils were assessed. The study emphasizes on isolation and screening of efficient PAE-utilizing fungi for potent application in bioremediation of contaminated soils.